1998
DOI: 10.1007/bf02550272
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous (renal) pelvic rupture. Two cases cured by conservative therapy

Abstract: Two cases of spontaneous pelvic rupture are presented. In Case 1 (female, 49 years) and Case 2 (male, 63 years) the rupture was due to obstruction and tumorous compression of the ureter, respectively. Authors deal with the diagnostic difficulties and the possibility of a cure without open surgery. Conservative therapy (double-J ureteral catheter and pigtail catheter) was successful in both cases. The pertinent literature is briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Stavodimos K, et al [10] reported on five patients managed successfully with a D-J ureteral stent insertion under fluoroscopy. Csata S, et al [19] reported 2 patients with spontaneous ureteral rupture cured by conservative therapy. Akpinar H, et al [8] successfully managed one patient by a D-J stent, one patient with acute urinary retention by urethral catheterization and 2 patients by conservative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Stavodimos K, et al [10] reported on five patients managed successfully with a D-J ureteral stent insertion under fluoroscopy. Csata S, et al [19] reported 2 patients with spontaneous ureteral rupture cured by conservative therapy. Akpinar H, et al [8] successfully managed one patient by a D-J stent, one patient with acute urinary retention by urethral catheterization and 2 patients by conservative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, there are successful renal-sparing techniques described for treating pelvic rupture, including renal decompression with ureteral and nephrostomy catheters with or without surgical repair (Csata et al 1998, Ashebu et al 2000, Murawski et al 2008, Battista et al 2016. Such techniques are available and could be considered for future feline clinical cases in order to preserve remaining renal function.…”
Section: Discusssionmentioning
confidence: 99%
“…The severity of disease tends to depend on whether disease is uni-or bilateral, whether there is partial or complete obstruction and the chronicity of the condition (Wilson 1977). In humans, there are rare reports of increased pressure within the renal cavity system causing renal pelvis rupture in association with ureteral calculi, trauma, tumours, pregnancy and spontaneously (Csata et al 1998;Ashebu et al 2000;Murawski et al 2008;Battista et al 2016 andYoung-Woong et al 2007). In many of the reported cases, there was a delay in diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous drainage of urinomas alone may be effective in a few cases too, but it is inadequate if the urinoma is caused by a ureteric obstruction. So, in the majority of the cases, placement of a ureteric stent in combination with percutaneous drainage of the urinoma is a rationalistic and effective therapy [2,6]. Nephrectomy is limited in cases of failure of conservative therapy and in septic life-threatening conditions.…”
mentioning
confidence: 99%